2022
DOI: 10.1111/aab.12774
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating effect of different photosynthetic pigments on Lipaphis erysimi preference and population build‐up on diverse Brassica juncea genotypes

Abstract: Brassica juncea is the most important oilseed crop in India, and Lipaphis erysimi is a major pest of this crop. The study aimed at knowing the role of photosynthetic pigments in host preference and population build‐up by L. erysimi on diverse B. juncea genotypes. We found significant differences among test genotypes for aphid preference, multiplication rate and population build‐up, and chlorophyll A, chlorophyll B, total chlorophyll, total carotenoids and Soil Plant Analysis Development (SPAD) chlorophyll and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Furthermore, a significant and positive association amid chlorophyll A and siliquae preference suggests that chlorophyll A is involved in the establishment of L. erysimi . Similarly, previous studies have shown a significant reduction in chlorophyll content in B. juncea genotypes due to L. erysimi feeding, as well as a positive association with L. erysimi population build‐up (Samal et al., 2022). Furthermore, greenbug feeding reduced chlorophyll levels in the host plant, affecting the photosynthetic process (Ma et al., 1998).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, a significant and positive association amid chlorophyll A and siliquae preference suggests that chlorophyll A is involved in the establishment of L. erysimi . Similarly, previous studies have shown a significant reduction in chlorophyll content in B. juncea genotypes due to L. erysimi feeding, as well as a positive association with L. erysimi population build‐up (Samal et al., 2022). Furthermore, greenbug feeding reduced chlorophyll levels in the host plant, affecting the photosynthetic process (Ma et al., 1998).…”
Section: Discussionsupporting
confidence: 64%
“…In addition, selecting and establishing a suitable host plant are essential phases in the interaction between insects and plants (Thorsteinson, 1960). It is primarily regulated by visual cues, which mostly consist of photosynthetic pigments (Dilawari & Atwal, 1989; Hardie, 1980; Samal et al., 2022). Aphids use olfactory cues to locate hosts, while visual cues are more important (Finch & Collier, 2000; Kostal & Finch, 1994; Prokopy & Owens, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these pigments are also implicated in the plant's response to various stresses. Previous studies have shown the disruption of chloroplast function and changes in the contents of chlorophylls and carotenoids could influence aphid feeding preferences, multiplication rate, and population build‐up (DeBlasio et al, 2018; Ipsita et al, 2022). Given that ntmyb35 mutant plants were more susceptible to aphid infestation in the field, we conducted an evaluation of aphid resistance in wild‐type, overexpression, and mutant plants by inoculating them with an equal number of aphids under controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The parthenogenetic viviparity, high fecundity, and host specificity support L. erysimi to multiply faster on Brassica plants. The interaction between olfactory cues like plant volatiles and visual stimuli including photosynthetic pigments are crucial for host plant finding by the aphids ( Hardie, 1980 ; Dilawari and Atwal, 1989 ; Samal et al, 2022 ). Due to non-availability of aphid resistance sources in the primary gene pool of brassicas ( Rana, 2005 ), the only effective and easily available strategy to control this pest is through systemic insecticides ( El-Wakeil et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%